The challenges and pathways to mainstreaming gender in Nigerian’s water sector governance - Appiah, Sarah; Osei-Amponsah, Charity; Sanchez Ramirez, Juan Carlos; Andam, Kwaw S. (International Water Management Institute, 2025)
Water scarcity in Nigeria exacerbated by population growth and climate change disproportionately affects women, girls, and other marginalized groups. This underscores the need for gender-responsive water governance. Drawing on research conducted by the International Water Management Institute (IWMI) under the CGIAR Policy Innovations Science Program, this blog shares insights on the challenges of gender integration in Nigeria’s water sector policies and institutions, with case studies from Abuja (FCT), Oyo, and Nasarawa States. Findings reveal persistent gaps despite existing policies, including weak regulatory enforcement, limited sex-disaggregated data, low institutional capacity for gender mainstreaming, and cultural resistance. The blog highlights key pathways forward, emphasizing inclusive policy design, improved data systems, capacity building, and coordinated action across government and stakeholders to advance inclusive and sustainable water governance.